LEGALISING EARLY CHILDHOOD DEVELOPMENT CENTERS IN THE EKURHULENI REGION - Nkambule, Modiegi Lydia (My University, 2012)
Despite all the legislative frameworks and policies in place for Early Childhood Development Centers to be registered, where benefits for registrations are outlined, there are lists which indicate that many are still unregistered, especially from the informal settlements. It is in these settlements that parents are mostly poor and in many cases unemployed, without any source of income, and owners are therefore not even accessing the benefits outlined. Ekurhuleni is one of the regions in Gauteng where such problems exist. It is also unknown or no information is available on the challenges that may be impeding the progress of the legalisation and registration of these Centers. Therefore, the aim of this research was to undertake an explorative study aiming at identifying and documenting challenges that the Gauteng Department of Social Development in the Ekurhuleni Region may be face, thus contributing to the delays in legalising and registering Early Childhood Development Centers (ECD’s
MM thesis - P&DM
Keywords: Early childhood development centres; Kindergartens; Pre-primary schools